2015
DOI: 10.5194/amt-8-5063-2015
|View full text |Cite
|
Sign up to set email alerts
|

ACTRIS ACSM intercomparison – Part 1: Reproducibility of concentration and fragment results from 13 individual Quadrupole Aerosol Chemical Speciation Monitors (Q-ACSM) and consistency with co-located instruments

Abstract: Abstract. As part of the European ACTRIS project, the first large Quadrupole Aerosol Chemical Speciation Monitor (Q-ACSM) intercomparison study was conducted in the region of Paris for 3 weeks during the late-fall -early-winter period (November-December 2013). The first week was dedicated to the tuning and calibration of each instrument, whereas the second and third were dedicated to side-by-side comparison in ambient conditions with co-located instruments providing independent information on submicron aerosol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
125
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 122 publications
(138 citation statements)
references
References 70 publications
(101 reference statements)
11
125
0
2
Order By: Relevance
“…Low abundance has been cited as the reason for highly variable measurements of ambient particulate chlorine using ACSM and similar instruments (Crenn et al, 2015). Overall, our results indicate that the standard operating procedure of the ACSM and similar instrumentation may systematically underestimate particulate chlorine concentration.…”
Section: Particulate Organochloridementioning
confidence: 54%
See 1 more Smart Citation
“…Low abundance has been cited as the reason for highly variable measurements of ambient particulate chlorine using ACSM and similar instruments (Crenn et al, 2015). Overall, our results indicate that the standard operating procedure of the ACSM and similar instrumentation may systematically underestimate particulate chlorine concentration.…”
Section: Particulate Organochloridementioning
confidence: 54%
“…The empirical correlations were derived using a comprehensive collection of aerosol mass spectrometer data sets but may underestimate O : C values for SOA formed under low-NO x conditions from isoprene or toluene . Variability in f 43 and f 44 among different ACSMs has also been reported (Crenn et al, 2015).…”
Section: Discussionmentioning
confidence: 98%
“…It must be noted, however, that the uncertainties of mass concentrations with aerosol mass spectrometers are estimated at 20-35 % (2σ ) for the total mass (Bahreini et al, 2009). Furthermore, Crenn et al (2015) reported reproducibility-related uncertainties of Q-ACSM concentration measurements of 9, 15, 19, 28 and 36 % for NR PM 1 , nitrate, organic matter, sulfate and ammonium, respectively, during an intercomparison that involved 13 Q-ACSMs in the Paris area during springtime. In addition to the relative ion transmission efficiency correction applied using a naphthalene internal standard, the collection efficiency (CE) due to particle losses induced by an incomplete vaporization and/or transmission through the aerodynamic lens was also determined for the whole dataset.…”
Section: Acsmmentioning
confidence: 99%
“…The Q-ACSM determines quantitative mass spectra of nonrefractory (NR) particles up to mass to charge ratios (m/z) of 150 (Crenn et al, 2015;Ng et al, 2011). Ion fragments were attributed mainly to organic aerosols, nitrate, sulfate, ammonium, and chloride, which comprise the reported data used in this study.…”
Section: Q-acsmmentioning
confidence: 99%